Neuroanatomical interpretation of Peter Paul Rubens’s copy of ,,The Battle of Anghiari’’ by Leonardo da Vinci - Keshelava, Grigol (European Scientific Journal, ESJ, 2020)
The object of this research is a drawing by Peter Paul Rubens, a copy of ,,The Battle of Anghiari’’ performed by Leonardo da Vinci in 1503-1506. This work, dating from 1603, was based on an engraving of 1553 by Lorenzo Zacchia, which was taken from a cartoon by Leonardo da Vinci. The original fresco itself is lost. Since the individual details of the drawing matched the anatomical elements of the human brain we decided to perform an anatomical interpretation. With the help of the program Paint X we were able to move 23 elements of the drawing. The comparison revealed the similarity between the details of the obtained image and the anatomical elements of the brain. Our research shows that the Peter Paul Rubens’s copy of ,,The Battle of Anghiari’’ by Leonardo da Vinci is a harmonious mix of Art and Anatomy. We have established that the copy of the lost fresco, which was created six centuries ago, includes double content. By moving 23 details of the drawing in which the battle is depicted, an image is obtained. This image accurately describe the anatomical elements of the brain in the lateral view.